Clinical pharmacology of single‐ and multiple‐ascending doses of ACT‐178882, a new direct renin inhibitor, and its pharmacokinetic interaction with food and midazolam. (31st July 2012) - Dingemanse, Jasper; Nicolas, Laurent; Binkert, Christoph
Abstract: This study investigated the tolerability, safety, pharmacokinetics, and pharmacodynamics of ACT‐178882, a new direct renin inhibitor, as well as its interaction with food and midazolam. Healthy male subjects received either single (10–1000 mg) or multiple doses (30–600 mg) administered once daily for 14 days of ACT‐178882, placebo, or 20 mg enalapril in the fasted state. Following a 2‐week washout, the single dose of 30 mg ACT‐178882 was also administered in the fed state. In the multiple‐ascending‐dose part, subjects were dosed with midazolam on days −2, 2, and 12 to investigate interactions with CYP3A4. Dizziness and headache were the most frequently reported adverse events. No clinically relevant changes occurred for body weight, vital signs, clinical laboratory variables, and ECG although both enalapril and ACT‐178882 tended to decrease systolic blood pressure. Following single doses of ACT‐178882, t 1/2 and t max varied from 18.7 to 24.7 h and from 3 to 5 h, respectively, and food had no significant effect. Steady‐state conditions were achieved after 4–6 days of dosing and accumulation was minimal. ACT‐178882 pharmacokinetics were dose proportional. ACT‐178882 but not enalapril dose‐dependently increased C max and area under the concentration‐time curve of midazolam. Single and multiple doses of ACT‐178882 dose‐dependently increased active renin and decreased plasma renin activity, whereas enalapril increased both variables. No effects on urinary excretion of creatinine, potassium, and the 6β‐hydroxycortisol/cortisol ratio were observed, whereas sodium and aldosterone excretion was decreased by both ACT‐178882 and enalapril. The current results with ACT‐178882 warrant further clinical investigation of this renin inhibitor in hypertensive patients.